SEMIOTIC ANALYIS ON SAGA TRADITIONAL HOUSE IN SAGA VILLAGE (SAUSSURE’S AND PEIRCE’S PERSPECTIVE) - Kasimo, Yulius Y (Lantern: Journal of Language and Literature, 2025)
Analyzing the meaning of sign on a traditional house is essential as language is part of the semiotic system in society. It is also an effort to preserve the local cultural values. This research investigates the meaning of the sign on the Saga traditional house. The methodology employed is descriptive qualitative that aims to explore, understand, and interpret the meaning of each sign associated with complex human experience, behaviors, cultures, and social phenomena. The principal finding of this research is that the meaning of signs is related to social protection, leadership, authority, ownership, social welfare, women's preservation and beauty, cultural strength, resilience, and defensiveness. Moreover, this research demonstrated that the preservation of the meaning of the signs becomes the medium of social communication between the local community and the ancestors. This research recommends that to improve the comprehension of language meaning, it is crucial to incorporate the conceptual understanding of semiotic meaning on social and cultural features into the linguistics courses.